The Relationship of Family Support to Fluid Restriction Compliance in Renal Failure Patients - Saputri, Agustina; Duha, Agusniar; Zega, Pelianus; Buarnirun, Yayutina; Iradewi, Iradewi (Jurnal Keperawatan Profesional, 2025)
Renal failure is a chronic disease that requires long-term management, including fluid intake restrictions. Patient compliance with fluid restrictions is crucial to prevent complications, but it is often difficult to achieve without family support. This study aims to investigate the relationship between family support and compliance with fluid restrictions among kidney failure patients undergoing hemodialysis at private hospital in Indonesia.  The method used was quantitative with a correlational approach and  simple purposive sampling technique. The sample consisted of 132 patients, with questionnaire to measure family support and the Interdialytic Weight Gain sclae to assess compliance.  Data analysis used Spearman’s rho test. The results showed no significant relationship  between family support and fluid restriction compliance (p = 0.217; r = 0.108). Family support was predominantly in the good category, while fluid restriction compliance was in the moderate category. Further research is recommended using qualitative methods and a larger sample size to gain a deeper understanding of the form of family support and its relationship  with patient compliance in undergoing hemodialysis.